Electric property evidences of carbonification of organic matters in marine shales and its geologic significance: A case study of the Lower Cambrian Qiongzhusi shale in the southern Sichuan Basin - Yuman Wang; Dazhong Dong; Xiangzhi Cheng; Jinliang Huang; Shufang Wang; Shiqian Wang (Natural Gas Industry B, 2014)
Searching for some reliable evidences that can verify the carbonification of organic matters in marine shales is a major scientific issue in selecting shale gas fairways in old strata. To this end, based on core, logging and testing data, the electric property of two organic-rich shale layers in the Lower Cambrian Qiongzhusi Fm. and the Lower Silurian Longmaxi Fm. in the southern Sichuan Basin was compared to examine the carbonification signs of organic matters in the Qiongzhusi shale and its influence on gas occurrence in the shales. The following conclusions were reached: (1) the electric property experiment shows that the Qiongzhusi shale in the study area has had carbonification of organic matters. The low resistivity of dry samples from this highly mature organic-rich shale and ultra-low resistivity on downhole logs can be used to directly judge the degree of organic matter carbonification and the quality of source rocks; (2) in the Changning area, the Qiongzhusi shale shows low resistivity of dry samples and low to ultra-low resistivity on logs, indicating that organic matters are seriously carbonized, while in the Weiyuan area, the Qiongzhusi shale shows a basically normal resistivity on log curves, indicating its degree of graphitization between the Longmaxi Fm. and Qiongzhusi Fm. in the Changning area; (3) shale with medium-to-high resistivity is remarkably better than that with ultra-low resistivity in terms of gas generation potential, matrix porosity and gas adsorption capacity; (4) industrial gas flow has been tested in the organic shales with medium-to-high resistivity in the Jianwei–Weiyuan–Tongnan area in the north, where the Qiongzhusi shale is a favorable shale gas exploration target.